2019
DOI: 10.5582/bst.2019.01197
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus IE2 protein regulates macrophage-mediated immune escape by upregulating GRB2 expression in UL122 genetically modified mice

Abstract: Although cytomegalovirus (HCMV) infection is asymptomatic in healthy individuals, the virus can remain latent for many years due to its ability to evade host immune surveillance. However, reactivation of HCMV can lead to life-threatening disease. Recent studies have shown that HCMV infection mediates immune escape by regulating macrophage activity, although the role of the HCMV-encoded IE2 protein is unclear. A ul122 transgenic mouse model was created to stably expresses the IE2 protein, and the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Human cytomegalovirus IE2 protein increases the expression of M2 Mø-linked cytokines IL-4 and IL-13 by up-regulating the expression of UL122, thereby promoting Mø-mediated immune escape. 31 This work found that high AIM2 expression in LUAD Mø promoted PD-L1 expression to repress immune infiltration of CD8 + T cells, thereby fostering tumor immune escape.…”
Section: Discussionmentioning
confidence: 85%
“…Human cytomegalovirus IE2 protein increases the expression of M2 Mø-linked cytokines IL-4 and IL-13 by up-regulating the expression of UL122, thereby promoting Mø-mediated immune escape. 31 This work found that high AIM2 expression in LUAD Mø promoted PD-L1 expression to repress immune infiltration of CD8 + T cells, thereby fostering tumor immune escape.…”
Section: Discussionmentioning
confidence: 85%
“…IE often serve as transcription factors that regulate the expression of both viral and host cellular genes, which are crucial for efficient viral replication. IE can also activate production of early and late structural viral proteins, including the viral tegument protein pp65 [20]. HCMV-pp65 is an immunomodulatory protein.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV-IE often serves as transcription factors that regulate the expression of both viral and host cellular genes, which are crucial to efficient viral replication. IE can also activate production of early and late structural viral proteins, including the viral tegument protein pp65 [22]. HCMV-pp65 is an immunomodulatory protein.…”
Section: Discussionmentioning
confidence: 99%